2022
DOI: 10.3389/fphys.2022.860868
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Altered Textural Property in Woody Breast Myopathy Using an Integrative Omics Approach

Abstract: Woody breast (WB) is a myopathy observed in broiler Pectoralis major (PM) characterized by its tough and rubbery texture with greater level of calcium content. The objective of this study was to investigate the functionality/integrity of WB sarcoplasmic reticulum (SR), which may contribute to the elevated calcium content observed in WB and other factors that may influence WB texture. Fourteen Ross line broiler PM [7 severe WB and 7 normal (N)] were selected, packaged, and frozen at −20°C at 8 h postmortem from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 100 publications
(132 reference statements)
0
1
0
Order By: Relevance
“…Our result showed that the ROS level and MDA content were increased in SR of WB-affected PM muscle. Welter et al (2022) noted a compromised structure of SR in the PM muscle WB myopathic bird, as evidenced by the alterations of the phospholipid membrane composition and increased lipid catabolism. These results suggested that excessive ROS in SR caused the oxidative damage of WB SR. Inositol 1,4,5-trisphosphate receptors ( IP3Rs ) and ryanodine receptors ( RyRs ) on SR membrane are the major Ca 2+ release channels that release Ca 2+ from SR into the cytoplasma, which is recovered by sarco endoplasmic reticulum Ca 2+ -ATPase ( SERCA ) ( Maklad et al, 2019 ).…”
Section: Discussionmentioning
confidence: 96%
“…Our result showed that the ROS level and MDA content were increased in SR of WB-affected PM muscle. Welter et al (2022) noted a compromised structure of SR in the PM muscle WB myopathic bird, as evidenced by the alterations of the phospholipid membrane composition and increased lipid catabolism. These results suggested that excessive ROS in SR caused the oxidative damage of WB SR. Inositol 1,4,5-trisphosphate receptors ( IP3Rs ) and ryanodine receptors ( RyRs ) on SR membrane are the major Ca 2+ release channels that release Ca 2+ from SR into the cytoplasma, which is recovered by sarco endoplasmic reticulum Ca 2+ -ATPase ( SERCA ) ( Maklad et al, 2019 ).…”
Section: Discussionmentioning
confidence: 96%